MODERN HIGHER EDUCATION IN THE CONDITIONS OF COMPETITIVE EDUCATION MARKET: COMPARATIVE ANALYSIS OF EXPERIENCE OF COUNTRIES OF BLACK SEA REGION - Бобрицька, Валентина Іванівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article generalization of works of scientists, maintenance of modern normatively-legal principles is carried out in relation to determination of essence of concept «educational services» as complex of certain by a legislation, educational program or agreement of actions of subject of educational activity, that have a certain cost and sent to achievement of formation of the expected results of studies a bread-winner; the results of comparative analysis of experience of countries of the Black Sea region are presented from development of modern higher education in the conditions of increase of competition at the market of educational services